Hubungan Antara Aktivitas di Luar Ruangan dan Karakteristik Kesehatan Lansia - Retna Febri Arifiati; Endang Sri Wahyuni; Prasaja Prasaja (Jurnal Terapi Wicara dan Bahasa, 2026)
Background: Aging is a series of biological changes that occur in the body as we age and is characterized by a decline in physical abilities and an increased risk of disease. Increasing physical disorders can cause changes in the health of the elderly such as chronic diseases and complaints about the life they live such as the elderly becoming less active and tending to spend less time outdoors compared to their previous age. Several studies have shown positive results that exposure to activities carried out and the length of time spent outdoors on the health of the elderly. Objectives: The purpose of this study was to determine the relationship between outdoor activities and the health characteristics of the elderly at the Integrated Health Post (Posyandu) in Dukuh Tempuran, Bolon Village, Colomadu District, Karanganyar Regency, Central Java, Indonesia. Methods: This study used a quantitative method with a correlational research design. The study population was the Posyandu for the elderly in Dukuh Tempuran, Bolon Village, Colomadu District, Karanganyar Regency, Central Java, Indonesia, totaling 130 people. The sampling technique used incidental sampling technique obtained 105 people. Data collection used 2 questionnaires, namely the COPM questionnaire for the variable of functional independence characteristics and the Berg Balance Scale questionnaire for the variable of outdoor activities. Bivariate analysis using Chi-Square(X2). Results: Chi-Square(X2) statistical test results obtained a p-value of 0,001 (p < 0,05) X2= 35,452), which means there is a relationship between outdoor activities and the health characteristics of the elderly at the Dukuh Tempuran Integrated Health Post, Bolon Village, Colomadu District, Karanganyar Regency, Central Java, Indonesia. Conclusion: Outdoor activities have an important protective role for the health characteristics of the elderly. Therefore, the provision of accessible green open spaces and social support is crucial to facilitate an active lifestyle for the elderly. Keywords: Outdoor Activities, Health Characteristics, Elderly, Physical Activity.